The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Smoke on the Water: Comparative Assessment of Combined Thermal Shock Treatments for Control of Invasive Asian Clam, Corbicula fluminea - Neil E. Coughlan; Ross N. Cuthbert; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Gina Y. W. Vong; Emma Healey; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Jaimie T. A. Dick (Environmental Management, 2021)
Suppression of established populations of invasive alien species can be a complex and expensive process, which is frequently unsuccessful. The Asian clam, Corbicula fluminea (Müller, 1774), is considered a high impact invader that can adversely alter freshwater ecosystems and decrease their socioeconomic value. To date, C. fluminea continues to spread and persist within freshwater environments worldwide, despite repeated management attempts to prevent dispersal and suppress established populations. As extensive C. fluminea beds can often become exposed during low-water conditions, the direct application of hot or cold thermal shock treatments has been proposed as suitable mechanism for their control. Further, mechanical substrate disturbance may enhance the efficacy of thermal shock treatments by facilitating exposures to multiple layers of buried clams. In the present study, we advanced these methods by assessing combined applications of both hot and cold thermal shock treatments for control of C. fluminea , using steam spray (≥100 °C; 350 kPa), low- or high-intensity open-flame burns (~1000 °C) and dry ice (−78 °C). In a direct comparison of raking combined with hot thermal shock applications, both steam and high-intensity open-flame treatments tended to be most effective, especially following multiple applications. In addition, when hot thermal treatments are followed by a final cold shock (i.e. dry ice), steam treatments tended to be most effective. Further, when dry ice was applied either alone or prior to an application of a hot shock treatment, substantial if not complete C. fluminea mortality was observed. Overall, this study demonstrated that combined applications of hot and cold thermal shock treatments, applied following the disruption of the substrate, can substantially increase C. fluminea mortality compared to separate hot or cold treatments.

Steam and Flame Applications as Novel Methods of Population Control for Invasive Asian Clam (Corbicula fluminea) and Zebra Mussel (Dreissena polymorpha) - Neil E. Coughlan; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Emma Healey; Jaimie T. A. Dick; Gina Y. W. Vong; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Ross N. Cuthbert (Environmental Management, 2020)
Control strategies for established populations of invasive alien species can be costly and complex endeavours, which are frequently unsuccessful. Therefore, rapid-reaction techniques that are capable of maximising efficacy whilst minimising environmental damage are urgently required. The Asian clam ( Corbicula fluminea Müller, 1774), and the zebra mussel ( Dreissena polymorpha Pallas, 1771), are invaders capable of adversely affecting the functioning and biodiversity of freshwater ecosystems. Despite efforts to implement substantial population-control measures, both species continue to spread and persist within freshwater environments. As bivalve beds often become exposed during low-water conditions, this study examined the efficacy of steam-spray (≥100 °C, 350 kPa) and open-flame burn treatments (~1000 °C) to kill exposed individuals. Direct steam exposure lasting for 5 min caused 100% mortality of C. fluminea buried at a depth of 3 cm. Further, combined rake and thermal shock treatments, whereby the substrate is disturbed between each application of either a steam or open flame, caused 100% mortality of C. fluminea specimens residing within a 4-cm deep substrate patch, following three consecutive treatment applications. However, deeper 8-cm patches and water-saturated substrate reduced maximum bivalve species mortality rates to 77% and 70%, respectively. Finally, 100% of D. polymorpha specimens were killed following exposure to steam and open-flame treatments lasting for 30 s and 5 s, respectively. Overall, our results confirm the efficacy of thermal shock treatments as a potential tool for substantial control of low-water-exposed bivalves. Although promising, our results require validation through upscaling to field application, with consideration of other substrate types, increased substrate depth, greater bivalve densities, non-target and long-term treatment effects.

Better off dead: assessment of aquatic disinfectants and thermal shock treatments to prevent the spread of invasive freshwater bivalves - Neil E. Coughlan; Stephanie J. Bradbeer; Ross N. Cuthbert; Eoghan M. Cunningham; Kate Crane; Stephen Potts; Joe M. Caffrey; Frances E. Lucy; Alison M. Dunn; Eithne Davis; Trevor Renals; Claire Quinn; et al. (Wetlands Ecology and Management, 2020)
Biosecurity protocols designed to prevent further spread of invasive alien species have become a key component of invader management strategies. Yet, the species-specific efficacy of many biosecurity treatments are frequently unclear or unknown. Invasive quagga, Dreissena bugensis , and zebra mussels, D. polymorpha , are a serious threat to freshwater ecosystems worldwide. Here, we examine the effectiveness of immersion (≤ 90 min) within 2% or 4% solutions for two commonly used disinfectants (Virasure® Aquatic and Virkon® Aquatic) to cause mortality of adult Dreissena bivalves . Further, we assessed the effectiveness of thermal treatments: steam spray (≥ 100 °C; ≤ 120 s); hot air (− 500 °C; ≤ 60 s); and dry ice exposure (− 78 °C; ≤ 300 g; 15 min). Complete mortality of D. polymorpha was observed following exposure to both disinfectants for 90 min, at both concentrations. However, high but incomplete mortality (40–90%) was recorded for D. bugensis across disinfectant treatments. For both species, complete mortality was achieved following 30 s of steam. In addition, 10 s of hot air and 15 min exposure to 300 g of dry ice can both completely killed groups of D. polymorpha . Overall, although the disinfectants did not cause complete mortality, it appears that relatively brief exposure to thermal treatments could be used to curtail the further spread of Dreissena species.

A reintroduced ecosystem engineer provides a germination niche for native plant species - Catherine E. Ross; Sue McIntyre; Philip S. Barton; Maldwyn J. Evans; Saul A. Cunningham; Adrian D. Manning (Biodiversity and Conservation, 2020)

Approaches to Landscape Scale Inference and Study Design - Ross B. Cunningham; David B. Lindenmayer (Current Landscape Ecology Reports, 2017)

Interaction rewiring and the rapid turnover of plant–pollinator networks - Paul J. CaraDonna; William K. Petry; Ross M. Brennan; James L. Cunningham; Judith L. Bronstein; Nickolas M. Waser; Nathan J. Sanders (Ecology Letters, 2017)
Whether species interactions are static or change over time has wide‐reaching ecological and evolutionary consequences. However, species interaction networks are typically constructed from temporally aggregated interaction data, thereby implicitly assuming that interactions are fixed. This approach has advanced our understanding of communities, but it obscures the timescale at which interactions form (or dissolve) and the drivers and consequences of such dynamics. We address this knowledge gap by quantifying the within‐season turnover of plant–pollinator interactions from weekly censuses across 3 years in a subalpine ecosystem. Week‐to‐week turnover of interactions (1) was high, (2) followed a consistent seasonal progression in all years of study and (3) was dominated by interaction rewiring (the reassembly of interactions among species). Simulation models revealed that species’ phenologies and relative abundances constrained both total interaction turnover and rewiring. Our findings reveal the diversity of species interactions that may be missed when the temporal dynamics of networks are ignored.

Ecological and socio-economic factors affecting extinction risk in parrots - George Olah; Stuart H. M. Butchart; Andy Symes; Iliana Medina Guzmán; Ross Cunningham; Donald J. Brightsmith; Robert Heinsohn (Biodiversity and Conservation, 2016)

Reforestation with native mixed‐species plantings in a temperate continental climate effectively sequesters and stabilizes carbon within decades - Shaun C. Cunningham; Timothy R. Cavagnaro; Ralph Mac Nally; Keryn I. Paul; Patrick J. Baker; Jason Beringer; James R. Thomson; Ross M. Thompson (Global Change Biology, 2015)
Reforestation has large potential for mitigating climate change through carbon sequestration. Native mixed‐species plantings have a higher potential to reverse biodiversity loss than do plantations of production species, but there are few data on their capacity to store carbon. A chronosequence (5–45 years) of 36 native mixed‐species plantings, paired with adjacent pastures, was measured to investigate changes to stocks among C pools following reforestation of agricultural land in the medium rainfall zone (400–800 mm yr −1 ) of temperate Australia. These mixed‐species plantings accumulated 3.09 ± 0.85 t C ha −1 yr −1 in aboveground biomass and 0.18 ± 0.05 t C ha −1 yr −1 in plant litter, reaching amounts comparable to those measured in remnant woodlands by 20 years and 36 years after reforestation respectively. Soil C was slower to increase, with increases seen only after 45 years, at which time stocks had not reached the amounts found in remnant woodlands. The amount of trees (tree density and basal area) was positively associated with the accumulation of carbon in aboveground biomass and litter. In contrast, changes to soil C were most strongly related to the productivity of the location (a forest productivity index and soil N content in the adjacent pasture). At 30 years, native mixed‐species plantings had increased the stability of soil C stocks, with higher amounts of recalcitrant C and higher C : N ratios than their adjacent pastures. Reforestation with native mixed‐species plantings did not significantly change the availability of macronutrients (N, K, Ca, Mg, P, and S) or micronutrients (Fe, B, Mn, Zn, and Cu), content of plant toxins (Al, Si), acidity, or salinity (Na, electrical conductivity) in the soil. In this medium rainfall area, native mixed‐species plantings provided comparable rates of C sequestration to local production species, with the probable additional benefit of providing better quality habitat for native biota. These results demonstrate that reforestation using native mixed‐species plantings is an effective alternative for carbon sequestration to standard monocultures of production species in medium rainfall areas of temperate continental climates, where they can effectively store C, convert C into stable pools and provide greater benefits for biodiversity.

The influences of climatic variation and vegetation on stream biota: lessons from the B ig D ry in southeastern A ustralia - James R. Thomson; Nick R. Bond; Shaun C. Cunningham; Leon Metzeling; Paul Reich; Ross M. Thompson; Ralph Mac Nally (Global Change Biology, 2012)
Aquatic biodiversity faces increasing threats from climate change, escalating exploitation of water and land use intensification. Loss of vegetation in catchments (= watersheds) has been identified as a substantial problem for many river basins, and there is an urgent need to better understand how climate change may interact with changes in catchment vegetation to influence the ecological condition of freshwater ecosystems. We used 20 years of biological monitoring data from V ictoria, southeastern A ustralia, to explore the influences of catchment vegetation and climate on stream macroinvertebrate assemblages. Southeastern A ustralia experienced a severe drought from 1997 to 2009, with reductions of stream flows >50% in some areas. The prolonged drying substantially altered macroinvertebrate assemblages, with reduced prevalence of many flow‐dependent taxa and increased prevalence of taxa that are tolerant of low‐flow conditions and poor water quality. Stream condition, as assessed by several commonly used macroinvertebrate indices, was consistently better in reaches with extensive native tree cover in upstream catchments. Prolonged drought apparently caused similar absolute declines in macroinvertebrate condition indices regardless of vegetation cover, but streams with intact catchment and riparian vegetation started in better condition and remained so throughout the drought. The largest positive effects of catchment tree cover on both water quality and macroinvertebrate assemblages occurred above a threshold of ca. 60% areal tree cover in upstream catchments and in higher rainfall areas. Riparian tree cover also had positive effects on macroinvertebrate assemblages, especially in warmer catchments. Our results suggest that the benefits of extensive tree cover via improved water quality and in‐channel habitat persist during drought and show the potential for vegetation management to reduce negative impacts of climatic extremes for aquatic ecosystems.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

A statistical methodology for tracking long-term change in reporting rates of birds from volunteer-collected presence–absence data - Ross Cunningham; Penny Olsen (Biodiversity and Conservation, 2009)

The Combined Effects of Remnant Vegetation and Tree Planting on Farmland Birds - ROSS B. CUNNINGHAM; DAVID B. LINDENMAYER; MASON CRANE; DAMIAN MICHAEL; CHRISTOPHER MacGREGOR; REBECCA MONTAGUE‐DRAKE; JOERN FISCHER (Conservation Biology, 2008)
Biodiversity conservation on agricultural land is a major issue worldwide. We estimated separate and joint effects of remnant native woodland vegetation and recent tree plantings on birds on farms (approximately 500–1000 ha) in the heavily cleared wheat and sheep belt of southern Australia. Much of the variation (>70%) in bird responses was explained by 3 factors: remnant native‐vegetation attributes (native grassland, scattered paddock trees, patches of remnant native woodland); presence or absence of planted native trees; and the size and shape of tree plantings. In terms of the number of species, remnant native vegetation was more important than tree planting, in a 3:1 ratio, approximately. Farms with high values for remnant native vegetation were those most likely to support declining or vulnerable species, although some individual species of conservation concern occurred on farms with large plantings. Farm management for improved bird conservation should account for the cumulative and complementary contributions of many components of remnant native‐vegetation cover (e.g., scattered paddock trees and fallen timber) as well as areas of restored native vegetation.

Accumulation of deicing salts in soils in an urban environment - Mary Ann Cunningham; Eric Snyder; Daniel Yonkin; Morgan Ross; Toren Elsen (Urban Ecosystems, 2008)

Mechanisms of competition: thermal inhibition of tree seedling growth by grass - Marilyn C. Ball; J. Egerton; Jason L. Lutze; Vincent P. Gutschick; Ross B. Cunningham (Oecologia, 2002)

Testosterone treatment suppresses paternal care in superb fairy-wrens, Malurus cyaneus, despite their concurrent investment in courtship - Anne Peters; Andrew Cockburn; Ross Cunningham (Behavioral Ecology and Sociobiology, 2002)

Comparative Effects of Ambient Ultraviolet‐B Radiation on Two Sympatric Species of Australian Frogs - Sara D. Broomhall; William S. Osborne; Ross B. Cunningham (Conservation Biology, 2000)
Declines have been observed in a number of Australian frog species, many of these at high elevations. Alpine regions in Australia are likely to be particularly subject to increases in ultraviolet‐B radiation ( UV‐B, 280–320 nm) because UV‐B levels increase with elevation and because anthropogenic depletion of ozone has been particularly severe in the southern hemisphere. We compared survivorship of embryos and tadpoles of a declining species of frog, Litoria verreauxii alpina , with those of a sympatric nondeclining species, Crinia signifera , under three ambient UV‐B treatments, unshielded, control, and UV‐B–excluding. Experiments were conducted in artificial water bodies established at three different elevations (1365, 1600, and 1930 m) in the Snowy Mountains of southeastern Australia. The exclusion of UV‐B significantly enhanced survival of L. v. alpina (declining species) at all elevations. Overall, the probability of dying was highest in the unshielded treatments and lowest under the UV‐B–excluding treatment for both species over all elevations. The probability of dying was significantly higher in L. v. alpina than in C. signifera for a given UV‐B treatment at the two highest elevations. Our results support the hypothesis that ultraviolet radiation is likely to be a contributing factor in the disappearance of L. v. alpina at high elevations in southern Australia.